RiCRN1, a Crinkler Effector From the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis, Functions in Arbuscule Development - Voß, Stefanie; Betz, Ruben; Heidt, Sven; Corradi, Nicolas; Requena, Natalia (Frontiers in Microbiology, 2018)
Arbuscular mycorrhizal (AM) symbiosis is one of the most prominent and beneficial plant-microbe interaction that facilitates mineral nutrition and confers tolerance to biotic and abiotic stresses. AM fungi colonize the root cortex and develop specialized structures called arbuscules where the nutrient exchange takes place. Arbuscule development is a highly controlled and coordinated process requiring the involvement of many plant proteins recruited at that interface. In contrast, much less is known about the fungal proteins involved in this process. Here we have identified an AM fungal effector that participates in this developmental step of the symbiosis. RiCRN1 is a crinkler (CRN) effector that belongs to a subfamily of secreted CRN proteins from R. irregularis. CRNs have been so far only functionally characterized in pathogenic microbes and shown to participate in processes controlling plant cell death and immunity. RiCRN1 accumulates during symbiosis establishment parallel to MtPT4, the gene coding for an arbuscule-specific phosphate transporter. Expression in N. benthamiana leaves and in M. truncatula roots suggest that RiCRN1 is not involved in cell death processes. RiCRN1 dimerizes and localizes to nuclear bodies, suggesting that, similar to other CRNs, it functions in the plant nucleus. Downregulation of RiCRN1 using host-induced gene silencing (HIGS) led to an impairment of the symbiosis in M. truncatula and to a reduction of MtPT4, while ectopic expression of RiCRN1, surprisingly, led to a drastic reduction in arbuscule size that correlated with a decrease not only in MtPT4 but also in MtBCP1, a marker for initial stages of arbuscule development. Altogether, our results suggest that a tightly regulated expression in time and space of RiCRN1 is critical for symbiosis progression and for the proper initiation of arbuscule development.